Public health law in Timor-Leste - Barclay, Lee (Curtin University, 2011)
Post-conflict, ‘fragile’ nations face significant health, social, economic and political challenges. The international community is, on the whole, organised and effective in assisting these nations to address urgent priorities. Often, however, prioritisation of immediate concerns has resulted in less focus being given to capacity building, including the fostering of lasting, effective and autonomous systems within these nations.This study examined the post-conflict, transitional nation of Timor-Leste. In particular, it focused on the potential for a health systems-strengthening approach, public health law, to improve the exceptionally poor level of population health found in Timor-Leste. Public health law has a long history within the developed world of success in facilitating the prevention and control of disease. The extent to which law can assist in addressing key health concerns within the developing world has, however, attracted little attention to date.This thesis documents a social and political history of Timor-Leste and provides a review of selected population health indicators. An overview of the Timorese health and legal systems is provided with a focus on system capacity, existing public health law and reported strategic directions. The review is complemented by a survey of 245 residents of Dili, the capital of Timor-Leste, in order to ascertain levels of community awareness of, and support for, selected existing public health laws. Further context was provided through in-depth interviews with 19 health and legal professionals living and working in Timor-Leste. Importantly the study was designed and conducted according to guidance provided by four Timorese cultural advisors.Awareness of law is clearly essential if it is to be effective as a preventive intervention. Community support for law is arguably also fundamental if there is to be widespread adherence to law and political willingness to pursue law reform. Key dependent variables within the community survey and interviews with professionals included awareness of, and support for, public health law amongst a suite of specific regulatory areas including road safety, the sale of alcohol and tobacco to children, food safety and water safety. These areas were selected due to their existing or steadily increasing importance in the developing world. Quantitative analytical methods included Chi-square for examining differences between survey sub-groups, and Kendall’s tau-b for examining correlations between ordinal variables. Qualitative data from interviews was subject to thematic analysis.Analysis of survey and interview data highlighted a poor level of awareness of selected existing public health laws in Timor-Leste amongst participating community members and health and legal professionals. A number of demographic factors were identified as being statistically associated with levels of awareness within the community and these provide direction for future educative efforts. Encouragingly, this study has also identified a strong level of support for public health law amongst both community and professional groups. Support was high for the legal approach to health law overall and for each of the regulatory areas examined. Attitudinal factors associated with community support were identified and these provide guidance for future efforts to raise understanding and acceptance of public health law in Timor- Leste.The review of the health and legal systems, however, highlights that there currently exists an incomplete set of laws that lacks cohesion and accessibility in Timor-Leste: an analysis of applicable law requires a detailed investigation of Timorese and Indonesian law, and United Nations regulations. There appears also to be little systemic capacity to enforce existing, or develop additional, law and regulation. Public health law reform, furthermore, does not appear to be among the Timor-Leste government’s strategic directions.This study is one of few undertaken globally on public health law in a developing, post-conflict transitional society. The observation of widespread support for the legal approach to health provides impetus and direction to the proposition of a coordinated and resourced public health law strategy in Timor-Leste. Recommendations have been provided to address some of the current barriers to such a strategy, including capacity constraints, low awareness and low political and public service profile. Finally a theoretical framework is provided to specifically guide further research and implementation of public health law in Timor-Leste and similar settings.